Lopez bay aqua eco-tourism center - Manas, Arthur G. (Manila : National University, 2000)
The DOT is in the process of setting the base for ecotourism development by conducting environmental management workshops in tourist areas in accordance with the Philippine tourism master plan.
Title page -- Letter of endorsement -- Jury's Approval sheet -- Acknowledgement -- Dedication -- Chapter I. Introduction -- Chapter II. Methodology -- Chapter III. Terms of references -- Chapter IV. Design framework -- Chapter V. Design Analysis and presentation -- Chapter VI. Conclusion and recommendation -- Bibliography -- Pictorial presentation of plates -- Appendices -- Profile of proponent.
Includes bibliographical references.
Keywords: ECO-TOURISM; CENTER